Alocação de recursos em comunidades carentes - Campos Tinoco, Paola Viviana (2024)
The allocation of resources in underserved communities is a complex task that requires a careful and inclusive approach. A gap in current research is the lack of consideration for residents' preferences in resource allocation methodologies, leading to poorly designed policies that may not adequately reflect the realities of the challenges faced by communities at the base of the pyramid. Furthermore, multicriteria decision-making is increasingly being used to support resource allocation in communities due to its ability to account for competing objectives, represent community preferences, and provide transparent resource allocation. In this context, the aim of this study was to apply a multicriteria methodology that integrates the perspectives of residents and decision-makers in resource allocation for underserved communities. The research was conducted in two stages: (1) analysis of residents' characteristics that influence their preferences for resources such as education, health, employment, and infrastructure, using statistical methods like ordinal logistic regression; and (2) integration of these preferences into an allocation framework based on the model proposed by Vieira (2024), validated through the EQUITY software in a case study in Votorantim-SP. The main findings indicated that demographic characteristics such as gender, age, and length of residence significantly influence residents' resource choices. Moreover, incorporating community preferences resulted in allocation strategies better aligned with local needs, demonstrating the feasibility and effectiveness of the proposed approach in supporting public managers in the formulation of more equitable policies.